(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2018)
The article proves that in Ukraine the system of social standards and guarantees needs to be optimized. The greatest influence on incomes among the instruments of their regulation is made by the minimum wage. It is proved that one of the directions of the regulation income system transformation in Ukraine is the change in the concept of salary formation. Improving the methodology for determining the optimal minimum wage makes it possible to optimize the system of social standards and guarantees in Ukraine.